Hubungan Norma Masyarakat dan Dukungan Pemerintah terhadap Keterampilan Wanita Tani dalam Pengelolaan Limbah pada Program P2L di Kota Bandar Lampung - Safitri, Yuli; Irawan, Sahrul Ari; Abdurrokhim, Muhammad (Universitas Galuh, 2025)
This study aims to examine the level of community norm support and government support in enhancing the waste management skills of women farmers within the Sustainable Food Yard Program (P2L) in Srengsem Subdistrict, Bandar Lampung City, as well as to analyze the relationship between social norms and government support with the skill level of women farmers in managing household waste in the same area. This research was conducted in November 2021 in Srengsem Subdistrict, Bandar Lampung City, involving a total sample of 40 respondents selected through purposive sampling, comprising all members of the Kenanga Women Farmers Group (KWT). The study utilized both primary and secondary data and employed a non-parametric statistical analysis using Spearman’s rank correlation. The results indicate that the level of support from community norms and government initiatives in improving the skills of women farmers falls within the moderate category. This suggests that existing community norms and government support have not yet been fully effective in empowering women farmers to independently carry out waste reduction and management. Furthermore, the level of support from both community norms and the government shows a significant relationship with the waste management skills of women farmers in the P2L program. This implies that stronger adherence to supportive social norms and higher levels of government involvement contribute positively to the enhancement of women's skills in managing household waste